2014
DOI: 10.1007/s11367-014-0807-1
|View full text |Cite
|
Sign up to set email alerts
|

LCA-based study on structural retrofit options for masonry buildings

Abstract: Purpose: Over the last decade, the rehabilitation/renovation of existing buildings has increasingly attracted the attention of scientific community. Many studies focus intensely on the mechanical and energy performance of retrofitted/renovated existing structures, while few works address the environmental impact of such operations. In the present study, the environmental impact of typical retrofit operations, referred to masonry structures, is assessed. In particular, four different structural options are inve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(9 citation statements)
references
References 22 publications
0
9
0
Order By: Relevance
“…At this point, real-world applications of retrofitting can be investigated to assess their environmental impacts [38]. Some studies [47,[51][52][53][54][55][56][57][58] focused on structural retrofitting of the existing building and their environmental impacts. Some [29,59] combine structural and sustainability metrics with economic terms implemented by monetizing CO 2 emissions.…”
Section: State Of the Art Of The Life Cycle Environmental Impact Assessment Of Vulnerable Buildingsmentioning
confidence: 99%
“…At this point, real-world applications of retrofitting can be investigated to assess their environmental impacts [38]. Some studies [47,[51][52][53][54][55][56][57][58] focused on structural retrofitting of the existing building and their environmental impacts. Some [29,59] combine structural and sustainability metrics with economic terms implemented by monetizing CO 2 emissions.…”
Section: State Of the Art Of The Life Cycle Environmental Impact Assessment Of Vulnerable Buildingsmentioning
confidence: 99%
“…57,118], in light of cradle-to-cradle design and circular economy approaches which have recently received increased attention as a valid and viable alternative to the traditional linear make-use-dispose paradigm. Intini and Kuehtz [55] investigated the use of recycled plastic bottles to manufacture thermal insulation in Italy and concluded that recycled polyethylene terephthalate (PET) can reduce environmental impact as much as 46% with respect to GWP.…”
Section: Ms8: Inclusion Of Waste By-product and Used Materials Intomentioning
confidence: 99%
“…Moreover, San-José Lombera & Aprea [52] emphasise that the sustainability of industrial buildings should not only be structured around energy consumption, but also include land, water, and material usage. The reuse potential is not covered substantially, but there is for example research showing that the recycling of building materials in masonry buildings generates environmental benefits due to avoided impact of virgin material production [55]. Related to reuse potential, Munarim et al [47] compare building rehabilitation with new building construction and disclose that the construction of a new office building would require about 250 years more to amortise total energy impacts when compared with the rehabilitation and transformation of an old hotel building to an office building.…”
Section: Ebp Categories and Kpismentioning
confidence: 99%